Large divergence and low diversity suggest genetically informed conservation strategies for the endangered Virgin Islands Boa (Chilabothrus monensis) (2015)
The Virgin Islands boa (Chilabothrus monensis) was listed as critically endangered by the U.S. Fish and Wildlife Service in 1979, and is presently known to occur in two disjunct regions: Isla de Mona and the eastern Puerto Rico Bank. Populations of the species are highly vulnerable and are hypothesized to have contracted considerably from their former range. Here we conduct intraspecific genetic analyses for this species using mitochondrial and nuclear loci as well as population genetic simulations. In so doing, we characterize nine microsatellite markers for C. monensis and demonstrate their potential usefulness for in situ or ex situ conservation genetic analysis. We find that populations on the Puerto Rico Bank are highly divergent (3.03% sequence divergence; 2.10 Mya temporal divergence) from Isla de Mona animals and that little genetic diversity exists within or among these sampling sites. Furthermore, we provide recommendations and an assessment of translocation/reintroduction potential for this species based on the genetic data presented herein. Our study also highlights the usefulness of simulations for assessing small sample size in conservation genetic studies. We anticipate that these results and genetic tools will be useful in formulating a comprehensive conservation genetic approach for Virgin Island boas. © 2015 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)